Construct validity of the Woodcock battery for language proficiency - Tapia Mendieta, Violeta (2002)
The study analizes the results of the Exploratory and Confirmatory Factorial Analysis of the subtests and areas of the Woodcock Language Proficiency Battery in order to determine its theorical validity. The participants were 541 students from 2th to 6th grades of public and private elementary schools. It was found that the Exploratory Factorial Analysis showed two factors: Factor 1, related to higher and complex linguistic processes such as categorization, meaning interpretation, analogical relationships and met comprehension. The Confirmatory Factor Analysis showed that the assumed model was valid The Exploratory Factorial Analysis of the areas (Oral Language, Reading and Written Language) showed they measure just one construct these obtained results were confirmed through the correspondent Factor Analysis.